2021
DOI: 10.1021/acsbiomaterials.0c01584
|View full text |Cite
|
Sign up to set email alerts
|

HepaRG Maturation in Silk Fibroin Scaffolds: Toward Developing a 3D In Vitro Liver Model

Abstract: In vitro liver models are necessary tools for the development of new therapeutics. HepaRG cells are a commonly used cell line to produce hepatic progenitor cells and hepatocytes. This study demonstrates for the first time the suitability of 3% silk scaffolds to support HepaRG growth and differentiation. The modulus and pore size of 3% silk scaffolds were shown to be within the desired range for liver cell growth. The optimal seeding density for HepaRG cells on silk scaffolds was determined. The growth and matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…In the past years, numerous in vitro models of the liver have been proposed, not only for fundamental research but also to support pharmaceutical development with reliable high-throughput platforms. , In this context, two-dimensional models of the liver, intended as monolayers of hepatic cells grown on flat substrates such as Petri dishes or multiwell plates, were the first platforms exploited to evaluate the hepatotoxic response to the administration of active pharmaceutical ingredients in vitro. These types of models, which can rely both on primary cells and cell lines, thus providing robust and reproducible results, led the way for the production of more complex models. , Up to now, some recent models have been based on three-dimensional cultures, where the cells are cultured within matrices mimicking the hepatic extracellular environment .…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, numerous in vitro models of the liver have been proposed, not only for fundamental research but also to support pharmaceutical development with reliable high-throughput platforms. , In this context, two-dimensional models of the liver, intended as monolayers of hepatic cells grown on flat substrates such as Petri dishes or multiwell plates, were the first platforms exploited to evaluate the hepatotoxic response to the administration of active pharmaceutical ingredients in vitro. These types of models, which can rely both on primary cells and cell lines, thus providing robust and reproducible results, led the way for the production of more complex models. , Up to now, some recent models have been based on three-dimensional cultures, where the cells are cultured within matrices mimicking the hepatic extracellular environment .…”
Section: Introductionmentioning
confidence: 99%
“…After 14 days of culture, the cells were passaged using 0.05% trypsin–EDTA. The HepaRG cell line was used for these experiments as it is a model liver cell line that has been previously used for liver TE applications 48–50 …”
Section: Methodsmentioning
confidence: 99%
“…The HepaRG cell line was used for these experiments as it is a model liver cell line that has been previously used for liver TE applications. [48][49][50]…”
Section: Heparg Culture Conditionsmentioning
confidence: 99%
“…demonstrated the suitability of SF lyophilized scaffolds to support the growth and differentiation of HepaRG cell, which is a commonly used cell line to produce hepatic progenitor cell and hepatocyte [ 156 ]. Results of the lipid droplet accumulation and expression of steatosis-related genes after exposure to oleic acid showed that the matrix support fabricated by 3% SF combined with HepaRG cells could be suitable for the construction of steatosis liver model [ 156 ]. By using a complex RSF scaffold fabricated by blending mulberry ( Bombyx mori ) SF with cell adhesion motif contained non-mulberry ( Antheraea assamensis ) SF, Janani et al.…”
Section: Advanced Biomedical Applications Of Rsf Materialsmentioning
confidence: 99%